Deconstructing intellectual curiosity. (June 2016) - Powell, Christopher; Nettelbeck, Ted; Burns, Nicholas R.
Abstract: Scales of Need for Cognition (NFC), Typical Intellectual Engagement (TIE), and Epistemic Curiosity (EC) measure intellectual curiosity (IC). These scales correlate strongly and have been factor-analyzed individually but not together. Here N = 396 (143 males) undergraduates completed measures of NFC, TIE, and EC. Six factors, labeled Intellectual Avoidance, Deprivation, Problem Solving, Abstract Thinking, Reading, and Wide Interest, were identified. TIE is the broadest scale, measuring all factors except Deprivation ; NFC measures Intellectual Avoidance and Problem Solving, plus Abstract Thinking and Deprivation to a lesser degree; and EC largely measures Deprivation . Moreover, Reading may not fit in the IC domain; higher-order factor analysis indicated that, whereas items measuring Reading loaded more strongly on their first-order factor, items measuring the other factors strongly loaded on a general factor of IC. These results are significant for understanding the contents of these scales, and for future scale development. Highlights: Six factors are found across three measures of intellectual curiosity (IC). Typical Intellectual Engagement measures all factors except Deprivation. Need for Cognition (18-item) measures Intellectual Avoidance and Problem Solving. Epistemic Curiosity largely measures Deprivation. Schmid–Leiman rotation indicates that Reading may not fit within the IC domain.